2020
DOI: 10.3389/fimmu.2020.570296
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Localization of Paneth Cells and Their α-Defensins in the Small Intestine of Adult Mouse

Abstract: Paneth cells contribute to intestinal innate immunity by sensing bacteria and secreting α-defensin. In Institute of Cancer Research (ICR) mice, α-defensin termed cryptdin (Crp) in Paneth cells consists of six major isoforms, Crp1 to 6. Despite accumulating evidences that α-defensin functions in controlling the intestinal microbiota, topographical localization of Paneth cells in the small intestine in relation to functions of α-defensin remains to be determined. In this study, we examined the expression level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 49 publications
2
23
0
Order By: Relevance
“…Alpha defensins are antimicrobial peptides active against a wide range of microorganisms [96]. Consistent with their known prevalence in the small intestine [97, 98], we documented higher expression of alpha defensin genes in the ileum compared with colon samples. Expression of several alpha defensins was higher in the Shank3B −/− KO mice compared to the wild-type mice, especially those on the supplemented zinc diet.…”
Section: Discussionsupporting
confidence: 86%
“…Alpha defensins are antimicrobial peptides active against a wide range of microorganisms [96]. Consistent with their known prevalence in the small intestine [97, 98], we documented higher expression of alpha defensin genes in the ileum compared with colon samples. Expression of several alpha defensins was higher in the Shank3B −/− KO mice compared to the wild-type mice, especially those on the supplemented zinc diet.…”
Section: Discussionsupporting
confidence: 86%
“…Consistent with their known prevalence in the small intestine [97,98], we documented higher expression of alpha defensin genes in the ileum compared with colon samples. Expression of several alpha defensins was higher in the Shank3B -/-KO mice compared to the wild-type mice, especially those on the supplemented zinc diet.…”
Section: Zinc Supplementation and Host Genotype In Uence Microbiota Compositionsupporting
confidence: 87%
“…Given the results that Crp4 administration rescued the dysbiosis and the impaired intestinal metabolites due to CSDS loading, it is suggested that Crp4 administration improved host microenvironment for Paneth cells and resulted in the increase of Crp1 secretion. This speculation is supported by evidence on the intestinal ecosystem, including that the intestinal commensal microbiota positively affects Paneth cell development and function, i.e., Crp secretions by comparing the germ-free and the conventional mice 12 , 48 , 49 .…”
Section: Discussionmentioning
confidence: 92%
“…α-Defensin, an antimicrobial peptide, produced and secreted by Paneth cells in the crypt of the small intestine is responsible, in part, for innate enteric immunity 9 12 and plays a critical role in both elimination and symbiosis in the intestine by killing pathogens while eliciting less bactericidal activities against commensal bacteria 13 . It has been reported that the absence of active α-defensin alters the composition of small intestinal microbiota in mice 14 , and oral administration of α-defensin rescues severe dysbiosis of graft-versus-host disease (GVHD) model mice 15 , indicating that α-defensin plays an important role in maintaining homeostasis of the intestinal microbiota.…”
Section: Introductionmentioning
confidence: 99%